PENGARUH FAKTOR FUNDAMENTAL MIKRO TERHADAP CAPITAL ADEQUACY RATIO - Irdawati Irdawati; Ansir Ansir; Sinarwati Sinarwati (Pascasarjana Universitas Halu Oleo, 2018)
This study aims to determine the effect of the micro fundamentals of financial ratios, namely profitability which is proxied by Return On Assets (ROA), Return On Equity (ROE), and Net Interst Margin (NIM), Efficiency proxied by Operational Efficiency (BOPO) Asset Quality proxied by Non-Performing Loans (NPL), and Liquidity proxied by the Loan to Deposit Ratio (LDR) to the Capital Adequacy Ratio (CAR) of Commercial banks listed on the Indonesia Stock Exchange. The period of observation in this study is 5 years, starting from 2011 to 2015. The population used in this study amounted to 43 banking companies listed on the Indonesia Stock Exchange in the period 2011-2015. The sample selection technique uses purposive sampling method, and 17 banking companies are used as samples. The data analysis technique used is multiple linear regression analysis. Processing data using Eviews 7 Based on the results of data analysis, partially ROA, ROE, NIM have an effect on and significant on CAR, BOPO, NPL, and LDR ratios that have no effect on CAR. Based on the ANOVA test, it is known that the F statistic is 9,061 with a significance of 0,000. Adjusted R-Square value is 0.371, this means that the ability of the independent variable in explaining the variation of the dependent variable is 37.1%, while the rest is explained by other variables outside the research model. Keywords: CAR, ROA, ROE, NIM, BOPO, NPL, & LDR